The Implementation of Student Team Achievement Division and Talking Stick on Economics Subject - Hasyim, Arwini (Classroom Action Research Journal (CARJO), 2018)
The change that happens in human is due to the learning process that makes when someone is studying, then, the better the response decreases. However, it is not consistent with those observed during the teaching practice SMAN 2 Batu. The problem is in terms of liveliness that the lack of participation of student during the learning takes place while in terms of achievement only 40% of student who passes the daily tests, while 60% did not pass. If that is allowed, then most students will not be able to continue to a higher class. Meanwhile, this study is conducted to determine the implementation of Student Team Achievement Division (STAD) and Talking Stick in order to enhance the activity and student achievement of Economic in SMAN 2 Batu. This study is a qualitative study. Data Student Team Achievement Division (STAD) and Talking Stick drawn from learning sheet, data was taken from the student activity sheet student activity and learning achievement is taken from the pretest and posttest.Keywords:Â Effectiveness. Learning Achievement, Student Team Achievement Division, Talking Stick